Cholesterol Levels Determine The Endocytic Route Followed By The Acetylcholine Receptor - Borroni, Maria Virginia (2010)
Stability of the nicotinic acetylcholine receptor (AChR) at the cell surface is critical to the correct functioning of the cholinergic synapse. Cholesterol (Chol) is an essential lipid that modulates AChR. We have studied the endocytosis of AChR in CHO-K1/A5 cells, a cell line heterologously expressing murine muscle adulttype receptor under different Chol membrane contents. Contrary to the norm, endocytosis of cell-surface AChR is accelerated by depletion of membrane Chol. This acceleration is no longer operative when membrane Chol levels are restored. We explored the possible mechanism involved in receptor loss in Chol depleted cells (Chol-). Under such conditions the AChR is internalized by a ligand-, clathrin- and dynamin independent mechanism, which does not involve the presence of the AChR-associated protein rapsyn. The small GTPase Rac1 is required: expression of a dominant negative form of Rac1, Rac1N17, abrogates receptor endocytosis. The accelerated internalization of AChR proceeds even upon disruption of the actin cytoskeleton and is furthermore found to require the activity of the small GTPase Arf6 and its effectors Rac1 and phospholipase D. Thus, membrane Chol appears to act as a key homeostatic regulator of cell-surface receptor levels, determining not only the rate but also the mechanism of AChR endocytosis